2020
DOI: 10.2478/aoas-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Salinity Levels on Water Quality, Growth Performance and Body Composition of Pacific White Shrimp (Litopenaeus vannamei Boone, 1931) Cultured in a Zero Water Exchange Heterotrophic System

Abstract: AbstractThe present study was aimed to evaluate the effects of different levels of salinity on water quality, growth performance, survival rate and body composition of Pacific white shrimp in a heterotrophic/biofloc technology (BFT). Shrimp post-larvae with an average weight of 74.46 mg were cultured in 300 L fiberglass tanks containing 130 L water at a density of 1 post-larva/L. Three treatments including different levels of salinity of 8, 21 and 32 ppt with three replicates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 61 publications
1
45
0
Order By: Relevance
“…Studies by various researchers have reported that the biofloc system improves the growth performance of cultured aquatics (Avnimelech and Kochba, 2009;Luo et al, 2014, Wang et al, 2015Mirzakhani et al, 2019;Khanjani et al, 2020b). The increase in growth performance in BFT24 treatment is possibly because of maintaining optimal water quality and continuous and fresh production of biofloc (Ekasari et al, 2010;Toledo et al, 2016).…”
Section: Growth Performance and Somatic Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies by various researchers have reported that the biofloc system improves the growth performance of cultured aquatics (Avnimelech and Kochba, 2009;Luo et al, 2014, Wang et al, 2015Mirzakhani et al, 2019;Khanjani et al, 2020b). The increase in growth performance in BFT24 treatment is possibly because of maintaining optimal water quality and continuous and fresh production of biofloc (Ekasari et al, 2010;Toledo et al, 2016).…”
Section: Growth Performance and Somatic Indicesmentioning
confidence: 99%
“…The lipid content of bioflocs is usually at the low level, but the presence of essential fatty acids has significantly increased their nutritional value (Ju et al, 2008;Khatoon et al, 2016). The type of carbon source (Khanjani et al, 2017), C: N ratio (Minabi et al, 2020), water salinity (Ekasari et al, 2010;Khanjani et al, 2020b), feeding level (Khanjani et al, 2016), the source of light and its intensity (Coyle et al, 2011), pH (Martins et al, 2019) and the type of microbial community (Ahmad et al, 2017) are considered as parameters affecting the biochemical composition of bioflocs.…”
Section: Proximate Composition Of Fish Body and Bioflocmentioning
confidence: 99%
See 1 more Smart Citation
“…Success in aquaculture is achieved by improving genetics, nutrition, immunity and disease control in farmed species. Parameters such as speci c growth rate, feed conversion ratio and survival rate play a key role in evaluating an aquaculture system (Ghaedi et al 2015, Khanjani et al 2020b). The use of immunostimulants is considered as an effective tool to overcome diseases and strengthen the immune system of farmed organisms (Meena et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A C/N ratio in the substrate ranging from 10 to 20 is considered optimal for heterotrophic bacteria to assimilate NH þ 4 -N (Goldman et al 1987;Avnimelech 1999;Avnimelech 2006;Avnimelech 2007;Crab et al 2012). Recently, supplying molasses (C/N of 15) to a shrimp based biofloc system resulted in an increase in the populations of heterotrophic bacteria, which caused a corresponding decline in the concentrations of ammonia and nitrite, respectively (Khanjani et al 2020c). Theoretically, 6.07 parts of organic carbon are required for heterotrophic bacteria to convert each part of NH þ 4 -N to biomass (NH Ebeling et al 2006).…”
Section: Introductionmentioning
confidence: 99%